PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - MANDATARI, RISKA B1021141112 (Jurnal Manajemen Update, 2017)
This research aims to test the influence of institutional ownership, managerial ownership, dividend policy and the policy of debt against the value of the company at the manufacturing companies listed on the Indonesia stock exchange period 2012-2016. The population in this research is the manufacturing companies listed on the Indonesia stock exchange. A sampling Technique used was purposive sampling that produced 13 companies as research samples. Methods of analysis used was multiple panel data regression analysis using EViews 9.This research uses 3 techniques of estimation of regression models to determine the best panel data of which that is a common effect Model, fixed effect models, and random effect models. The research found that fixed effect models were selected to estimate the variables are used as a determinant of the value of the company. The results of this study suggest that (1) the institutional Ownership has no effect against the value of the company, (2) managerial Ownership did not affect the value of the company, (3) the dividend policy has no effect against the value of the company, (4) debt Policy positive effect against the value of the company.Keywords: Institutional Ownership, Managerial Ownership, Dividend Policy, Debt Policy, Firm Value.